Postoperative pain control in cats: clinical trials with pre-emptive lidocaine epidural co-administered with morphine or methadone - Rossi, Rafael de; Hermeto, Larissa Correa [UNESP]; Jardim, Paulo Henrique Affonseca; Bicudo, Natalia de Andrade; Assis, Klebs Tavares de (SAGE Publications, 2015)
To evaluate the effectiveness of epidural lidocaine in combination with either methadone or morphine for postoperative analgesia in cats undergoing ovariohysterectomy. Under general anesthesia, 24 cats that underwent ovariohysterectomy were randomly allocated into three treatments groups of eight each. Treatment 1 included 2% lidocaine (4.0 mg/kg); treatment 2 included lidocaine and methadone (4.0 mg/kg and 0.3 mg/kg, respectively); and treatment 3 included lidocaine and morphine (4.0 mg/kg and 0.1 mg/kg, respectively). All drugs were injected in a total volume of 0.25 ml/kg via the lumbosacral route in all cats. During the anesthetic and surgical periods, the physiological variables (respiratory and heart rate, arterial blood pressure and rectal temperature) were measured at intervals of time zero, 10 mins, 20 mins, 30 mins, 60 mins and 120 mins. After cats had recovered from anesthesia, a multidimensional composite pain scale was used to assess postoperative analgesia at 2, 4, 8, 12, 18, and 24 h after epidural. The time to first rescue analgesic was significantly (P <0.05) prolonged in cats that received both lidocaine and methadone or lidocaine and morphine treatments compared with those that received the lidocaine treatment. All cats that received lidocaine treatment alone required rescue analgesic within 2 h of epidural injections. All treatments had significant cardiovascular and respiratory changes but they were within acceptable range for healthy animals during the surgical period. The two combinations administered via epidural allowed ovariohysterectomy with sufficient analgesia in cats, and both induced prolonged postoperative analgesia.